Power analysis of the basilar membrane in the cochlea by mechanical resonance - Jimenéz Hernández, M (Revista Mexicana de Ingenieria Biomedica, 2017)
This paper presents the power analysis to the mechanical model of the basilar membrane in the cochlea as a system of forced damped harmonic oscillators without lateral coupling proposed by Lesser and Berkeley. The Lagrange’s equation for dissipative mechanical systems and the energy method are used to obtain the general equation of the system. Next a solution by complex exponential is proposed using the resonance analysis considering only excitations of pure tones to obtain the equation of displacement, and with its derived the equation of velocity. The power in the system is the multiplication between the equations of the velocity and the excitation force. Finally the equation of the average power in the system is obtained. This new solution has the advantage of determining the relationship between the excitation frequency of the system and the position along the basilar membrane where the average power is maximum. This implies that the distance where there is a maximum transfer of energy between the wave propagating in the perilymph and the mechanical displacement of the basilar membrane on the hair cells in the organ of Corti is known. The power analysis is successfully compared with the two-dimensional model of the cochlea developed by Neely using finite differences and with the experimental results of Békésy. In both experiments are used the same mechanical parameters of the basilar membrane and the same set of frequencies of evaluation proposed in the original papers in order to compare the different methodologies.